Intergovernmentalgrantrules, the 'golden rule' of public finance and local expenditures - Pereira, Paulo Trigo (2010)
The Stability and Growth Pact and the process of fiscal consolidation in several European countries have enhanced the role of fiscal rules at sub-national level. This paper analyzes the combined effect of a rule to allocate capital and current block grants to local governments and the "golden rule" of public finance (surplus of current balance). We argue that the two fiscal rules introduce significant rigidities and distortions in local governments' expenditures structure since these mimic the structure of revenues. This effect is particularly relevant in municipalities that are more dependent of intergovernmental grants, mainly rural. On the other hand, urban municipalities with greater tax revenues (current revenues) are constrained in their ability to make capital investments because they receive per capita capital grants below what economies of scale would suggest. An empirical analysis of Portuguese local governments shows that it is no longer the median voter, but fiscal rules, that command the broad pattern of expenditure (current versus capital) at a local level. This paper is a contribution to the literature on the perverse effects of fiscal rules.